Nonunity gain minimal-disturbance measurement - Leuchs, Gerd; et al. (Physical Review A, 2007)
We propose and experimentally demonstrate an optimal nonunity gain Gaussian scheme for partial measurement of an unknown coherent state that causes minimal disturbance of the state. The information gain and the state disturbance are quantified by the noise added to the measurement outcomes and to the output state, respectively. We derive the optimal trade-off relation between the two noises and we show that the tradeoff is saturated by nonunity gain teleportation. Optimal partial measurement is demonstrated experimentally using a linear optics scheme with feedforward. © 2007 The American Physical Society.
UnivIS-Import:2015-03-09:Pub.2007.nat.dphy.optik.1optik.nonuni